Perceived Public Accounts Committee independence: the Malaysian case - Zainal Abidin, Zaharuddin; Muhammad Sori, Zulkarnain; Mat Daud, Zaidi; Senik, Rosmila (School of Business Innovation and Technopreneurship of Universiti Malaysia Perlis (UniMAP), 2019)
The objective of the study is to examine perceived Public Account Committee’s (PAC) independence from the perspective of PAC members and non-PAC members. The findings indicate that for the PAC to be independence, it should be free from any form of interference from any party when exercising and conducting its responsibilities. The PAC must be free to select any topic or issue to be examined that they think important and involves the public interest. However, being independent can also be seen as a way of gaining political mileage for PAC members and also gives advantages to the opposition members too. Overall, the independence of the PAC is still debatable judging from the decision and action of the government that PAC is seemed to be used as a government tool to cover the activities of the government. The move made by the government in appointing most of its representatives as well as the PAC chairman in the PAC as cabinet members seem to support the claimed that question the independence of the PAC.